2019
DOI: 10.1002/jbt.22342
|View full text |Cite
|
Sign up to set email alerts
|

Losartan delays the progression of streptozotocin‐induced diabetic cataracts in albino rats

Abstract: The ocular renin‐angiotensin system has become an interesting target for ocular diseases because it has been implicated in various ocular diseases such as diabetic retinopathy, glaucoma, age‐related macular degeneration, uveitis, and hypertensive cataracts. In the present study, we explored the effect of topically and orally administered losartan (an angiotensin receptor blocker) on streptozotocin‐induced diabetic cataract in albino rats. Topical treatment with losartan modulated neither the blood glucose leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The doses of RAS modulators were established based upon one patent study and our previous study. 4,34 We carried out pilot study on RAS modulators at four different concentration 0.1% w/v, 0.2% w/v, 0.5% w/v, and 1% w/v for each drugs. Results of pilot studies indicated 0.1% w/v and 0.2% w/v to be the least effective.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The doses of RAS modulators were established based upon one patent study and our previous study. 4,34 We carried out pilot study on RAS modulators at four different concentration 0.1% w/v, 0.2% w/v, 0.5% w/v, and 1% w/v for each drugs. Results of pilot studies indicated 0.1% w/v and 0.2% w/v to be the least effective.…”
Section: Methodsmentioning
confidence: 99%
“…We recently established that topically administered angiotensin receptor blocker (ARB) prevented the progression of streptozotocin (STZ)-induced formation of cataracts. 4 On the basis of our recent study, one may postulate that the local RAS in the eyes may intensify formation of cataracts in hyperglycemic conditions. In addition, the ocular RAS has become a unique pathway for the treatment and the prevention of various eyes related disorders.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Secondary complications with the eyes may elicit pathophysiological events in eyes' lenses and cause cataract formation, which corroborated the result of our previous studies. [8,15,17] Oxidative stress is a key factor in the generation of cataracts. [35] In this study, the Ang-II control group showed a significant elevation in lenticular oxidative stress as compared with the normal group.…”
Section: F I G U R E 4 Effects Of Ras Modulators On Lenticular Opacity: (A) Normal (B) Ang-ii Control (C) Arb (O) and (D) Arb (T) Ras Renmentioning
confidence: 99%
“…[ 12,14 ] In addition, various studies have revealed a possible link between the RAS and cataract formation; that is, RAS modulators, angiotensin receptor blockers (ARBs) and angiotensin‐converting enzyme inhibitors have been found to delay cataract formation in different cataract models. [ 7,15–17 ]…”
Section: Introductionmentioning
confidence: 99%